The history of the Irish in Britain: a bibliography, 1986 - Irish in Britain History Group, IBHG (1986)
Leaflet for the book launch, presented by the Irish in Britain History Group, to take place on 3 April 1986 at Camden Irish Centre. Event includes a talk by Sheridan Gilley, editor of 'The Irish in the Victorian city'. Year added by hand.